Early years physical activity and motor skills intervention: a feasibility study to evaluate an existing training programme for early years educators - Basterfield, Laura; Machaira, Theodora; Jones, Dan; Rapley, Tim; Araújo-Soares, Vera; Cameron, Neil; Azevedo, Liane B. (Children, 2023)
A lack of fundamental motor skills (FMS) in the early years can lead to lower engagement with physical activity (PA), and track into adulthood. This study aimed to test the feasibility of an existing intervention for Early Years Educators (“Educators”) designed to increase knowledge, confidence and the ability to increase PA and FMS of children in a deprived area of England. Non-randomised design with wait-list control. Sixty-seven settings in Middlesbrough, North East England were invited. Recruitment target: 10 settings, 2 Educators per setting, four children per Educator. Intervention: one-day training course “Physical Literacy in the Early Years”, an age-appropriate theoretical and practical training course to support the development of physical literacy. Primary outcomes: recruitment, retention, acceptability of intervention and outcome measures. Secondary outcomes: change in Educators’ knowledge, intentions and behaviour, and change in children’s BMI z-score, PA and FMS. Eight settings were recruited; all Intervention Educators completed the training. Six settings participated at follow-up (four Intervention, two Control). The target for Educator recruitment was met (two per setting, total n = 16). Questionnaires were completed by 80% of Intervention Educators at baseline, 20% at follow-up. Control Educators completed zero questionnaires. No Educators took part in a process evaluation interview. Forty-eight children participated at baseline, 28 at follow-up. The intervention was deemed acceptable. The recruitment, retention and acceptability of measurements were insufficient to recommend proceeding. Additional qualitative work is needed to understand and surmount the challenges posed by the implementation of the trial.